Analisa Pengaruh Biaya Promosi dan Harga Jual Terhadap Volume Penjualan pada Perusahaan Properti di Daerah Lampung - Riris Loisa, Andreas Aswin dan (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
Buying things is an activity that has been done since the first age of humanity. People buy things to fulfill living needs, may it be primary, secondary, or tertiary needs. At first humans used barter system, where people trade an item for another things, such as service or goods. Nowadays human uses money for buying things, and today, Indonesia economic power is rising among the globe. Based on that increase, people get more income, and upgrade their lifestyle. One of the things to buy for such need is property. When it comes to property, like other things, people will look into promotion and selling price, thus the two variables has been used for this research. The goal of this research is to understand whether those two variables has impact or not to selling volume. The data used for making this research is from a property company based in Lampung. The data was taken from the company annual yearly monetary report from year 2015 to 2018. One factor to take note is that the selling price was controlled by government since the company was selling government subsidiary backed houses, therefore the only variable that the company can fully control was the promotion cost. The conclusion was that the price doesn’t affect much of the selling volume, therefore the company should focus on better promotion programs.